Train + equip = peace? Stabilization requires more than capacity building - Claudia Major; Christian Mölling; Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2015)
Should Germany supply weapons to the Kurdish peshmerga forces battling Islamic State (IS)? This question aroused intense debate last summer, leading once more to the general issue of what role capacity building for third actors can play in crisis management. Germany wants to take on more responsibility in foreign policy but is keen to avoid direct military involvement as far as possible. Providing training and equipment for governments and regional organizations in crisis areas, enabling them to create and maintain peace and security by their own efforts, therefore seems sensible. The German Government has pursued this approach with its capacity building initiative ('Ertüchtigungsinitiative') since 2011, which was relabelled 'Enable and Enhance Initiative' in 2013. However, experience to date clearly reveals its risks and limitations. By providing training and equipment, Germany can make an important contribution to crisis management. But it is not a 'one size fits all' solution; on the contrary, it must be context-specific and geared towards long-term needs. (SWP Comments)
Keywords: 320